The Apocalyptic "Son of Man" in Daniel 7 - Ferch, A. J.
Diss.; director G. F. Hasel. 253 p. Order No. 7917878 chap. 2: alleged origins and parallels in other Near Eastern literatures; Diss Abstr 40 (1979-80) 215f.-A.